Developing a Scale for the Evaluation of People With Post-prandial Distress Syndrome - Xiao, Mengli; Ying, Jiake; Zhao, Yingpan; Zhao, Yang; Liu, Ying; Lu, Fang (Frontiers in Public Health, 2021)
Background: Functional dyspepsia (FD) is one of the most critical health problems worldwide. Although there has been an increased intervention to improve FD symptoms, it is difficult to compare the effect of intervention measures with the existing methods of reporting the outcome, and it is a lack of clinical evaluation tools that can be used to evaluate patients' symptoms and treatment. One way of potentially addressing this way is to offer a patient-reported symptom scoring scales, which can be self-reported by patients to highlight interventions' authenticity and reliability. Nevertheless, there is still a lack of validated patient-reported outcome instruments for post-prandial distress syndrome (PDS). This study aims to establish a symptom scoring scale to evaluate the effectiveness of interventions for PDS. Methods: The study consists of two steps. The first step was to formulate the scale. Through a systematic literature review and group discussion, an item pool and scale framework were formed. Then, through the expert consultation and pre-investigation, the formal version of the scale was formed. The second step is to test the reliability and validity of the scale. The scale is tested in the target population to determine whether the reliability and validity of the scale. Discussion: The improvement in patients' self-reported symptoms had a significant impact on the researchers' evaluation of the intervention's authenticity. Therefore, we develop a symptom scoring scale for reporting studies evaluating the effectiveness of PDS interventions. The scale will be used for a more significant comparison to evaluate PDS interventions' effectiveness. The scale also improves trial reporting, reducing research waste by prioritizing the collection and reporting of critical results for all relevant stakeholders. Clinical Trial Registration: ChiCTR, ChiCTR2100044489. Registered on March 22, 2021.